Optimasi Produksi dan Analisis Sensitivitas Produk “Bawang Goreng Crispy Yuk Riris” dengan Menggunakan Linear Programming - Roudlotul Badi'ah; Ahmad Syauqi; Rizna Ramadhani Winanda; Rusfian Effendi (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2022)
This study aims to optimize production using linear programming with graphical and simplex methods accompanied by sensitivity analysis to determine the optimal product combination with maximum profit for the "Bawang Goreng Crispy Yuk Riris". The data are sales, inventory, use of raw and additional materials, operations, and selling prices. The data analysis technique uses linear programming, graphs and simplex methods, and sensitivity analysis with the help of QM for Windows. The result shows that production optimization using linear programming graphical methods or simple graphs obtains the same results as the optimal solution of producing 713 packs of original crispy fried shallot and 333 packs of spicy fried shallot with a maximum profit of IDR 3.304.500.Sensitivity analysis shows that the solution remains optimal with the tolerance limit for the original taste from 0 to 3.500 and the spicy taste from 3.000 to infinity, and five production inputs are not optimal.